Eco-friendly synthesis and biological activity investigations of lead oxide nanoparticlesusing Rumex Nervosus Vahl leaf extract - Bidir Kassaw; Tadesse Bizuayehu; Mihret Kendie (Results in Chemistry)
The rise of antimicrobial resistance is a significant global health issue. Consequently, advancing green-based nanomedicines is an alternative solution for novel therapeutic options. To alleviate this problem, the bio-synthesized PbO NPs were successfully produced from an aqueous lead acetate and Rumex Nervosus Vahl leaf extract to identify the potential inhibitors. The qualitative phytochemical analysis of the leaf extract was screened by visual observation. The plant extract content, reaction temperature, reaction time, concentration of Pb(C2H3O2)2, and pH were first optimized for the synthesis of PbO NPs. The synthesized PbO NPs were characterized by UV–Vis, FT-IR, XRD, and TGA/DTA spectroscopic techniques. The average crystal size of the synthesized nanoparticles was found to be 41.464 nm. The in vitro antibacterial properties of the synthesized PbO NP exhibited significant activity against Bacillus (24.4 ± 0.2 mm), S. aureus (26.3 ± 0.1 mm), E. coli (24.6 ± 0.3 mm), and K. pneumoniae (27.8 ± 0.4 mm) using the disc diffusion method. Therefore, this results in the potential of PbO NPs as an effective new antibacterial drug agent, and future in vivo studies are needed to validate this drug.